SOCIO-ECONOMIC CONDITION OF THE FRUIT AND VEGETABLE NETWORK OF UZBEKISTAN AT THE BEGINNING OF INDEPENDENCE - Khasanov , Shakhboz (GOLDEN BRAIN, 2024)
This article deals with analysis of the socio-economic condition of agriculture of the Republic of Uzbekistan at the end of the 80s of the 20th century scientifically and historically, and instance of revealing the cotton monopoly implemented during the former union and its impact on the life of our country According to the results of the research of the scientific article, conclusions and suggestions were given based on a historical approach to the abolition of the cotton monopoly on the eve of independence and the role and prospects of the fruit and vegetable sector of agriculture in the life of our country.